2006
DOI: 10.1007/s10029-006-0127-x
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal tension-free repair of small midline ventral abdominal wall hernias with a Ventralex hernia patch: initial experience in 51 patients

Abstract: Midline ventral hernias are common. Tension-free mesh repair of ventral hernias is becoming popular due to the high recurrence rate with conventional techniques. We have used an open intraperitoneal technique using the Bard Ventralex hernia patch in midline ventral hernias ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 17 publications
4
26
2
Order By: Relevance
“…We had 2 hematomas without wound infection or seroma. These results compare favorably with the literature, with a mean infection rate of 2–4% [7,8]. We have found many advantages in using this technique, providing it is used with respect to specific indications.…”
Section: Commentsupporting
confidence: 79%
See 2 more Smart Citations
“…We had 2 hematomas without wound infection or seroma. These results compare favorably with the literature, with a mean infection rate of 2–4% [7,8]. We have found many advantages in using this technique, providing it is used with respect to specific indications.…”
Section: Commentsupporting
confidence: 79%
“…The mean duration of surgery in our study was 33 min, including the five interventions with concomitant procedures. These results are comparable (the time reported by Hadi et al [7] was 30 min) if not better than other published series (time reported by Martin et al [8] was 45 min) even though most operations were performed by residents helped by senior surgeons. Hospital stay in our study was 2 days (range 0–15).…”
Section: Commentsupporting
confidence: 76%
See 1 more Smart Citation
“…Two tails that are connected to the bilayer patch were sutured to fascial edges to avoid migration. Promising early results have been reported; however, these prostheses are expensive, and prospective randomized comparative studies have not yet been conducted (36)(37)(38). It has been reported that recurrence after this kind of bilayer prosthesis is higher in comparison with that after classical sublay mesh placements possibly because of the less controllable mesh deployment (39).…”
Section: Which Mesh?mentioning
confidence: 99%
“…This mesh, the Ventralex \ Hernia Patch (CR Bard, Murray Hill, NJ, USA; Fig. 1), was initially designed for the treatment of small ventral, umbilical, and epigastric hernias [6,7]. We currently employ this device to close all 15-mm trocar wounds.…”
Section: Introductionmentioning
confidence: 99%